Common variants of EDA are associated with non‐syndromic hypodontia. (7th September 2020) - Al‐Ani, Azza H.; Antoun, Joseph S.; Thomson, William M.; Topless, Ruth; Merriman, Tony R.; Farella, Mauro
Abstract: Objective: The aim of this case‐control study was to investigate the association between non‐syndromic hypodontia and nineteen common variants of candidate genes ectodysplasin A (EDA), paired box 9 (PAX9), msh homeobox 1 (MSX1) and axis inhibition protein 2 (AXIN2) . Settings and Sample Population: Sixty‐one hypodontia cases were frequency‐matched to 253 controls with no missing teeth (excluding the third molars). Material and Methods: Self‐report data and DNA samples were collected from each participant. Results: The sample had a mean age of 16.6 years (SD = 7.3), with most participants being female (59.6%), and of New Zealand European origin (75.4%). Using multiple logistic regression analysis, it was found that the T‐allele of rs12853659 (EDA) and the G‐allele of rs2428151 (EDA) were both associated with a higher risk of hypodontia (odds ratio, OR = 2.79, 95% CI = 1.11‐7.01; and OR = 2.87, 95% CI = 1.04‐7.94, respectively). The G‐allele of rs2520378 (EDA) showed a protective effect with an OR of 0.61 (95% CI = 0.38‐0.99). The EDA SNP findings were consistent with previous reports included in a meta‐analysis. No associations were found with the PAX9, AXIN2 and MSX1 genes, after adjusting for sex and ethnicity. Conclusions: Common variants of the EDA genes are associated with specific phenotypes of non‐syndromic hypodontia, thus confirming their role in the regulatory pathways of normal tooth development. However, larger samples are needed to investigate the association further.